Colorectal Cancer Surgery: Influence of Psychosocial Factors - Moldes-Moro, Regina; de Dios-Duarte, María José (Cancers, 2023)
(1) Background: In the treatment of colorectal cancer, it is important to consider different psychosocial factors. Our first objective was to measure the levels of perceived stress in subjects diagnosed with colorectal cancer awaiting potentially curative surgery. Also, we aimed to analyse what coping styles these patients used, how they perceived their illness, and the subsequent influence of these factors on their levels of stress. (2) Methods: Stress, coping styles and illness perception were assessed in a sample of 107 patients. The instruments used were the Perceived Stress Scale (PSS-14), the Stress Coping Questionnaire (SCQ) and the Brief Illness Perception Questionnaire (BIPQ-R). (3) Results: Patients using active coping styles have lower levels of perceived stress (p = 0.000; p = 0.002) than patients making use of passive coping styles (p = 0.000; p = 0.032; p = 0.001). A multi-linear regression model found that the perception of illness and the use of the negative approach coping style (p = 0.000; p = 0.001) influence an increase in perceived stress, and that a decrease in stress levels was influenced by the problem solving coping style (p = 0.001). (4) Conclusions: Based on our results, we recommend preventive interventions in care patients undergoing colorectal cancer surgery.